The isolated effect of midsole compliance on running economy and biomechanics in highly trained runners - Petrella, D.; Swinnen, W.; Tam, N.; Lane, B.; Vanwanseele, B. (Medicine & Science in Sports & Exercise, 2026)
Purpose: Running economy is a key determinant of endurance performance, with recently developed advanced footwear technologies (AFTs) improving running economy substantially. One key feature of AFTs is the thick, compliant midsole. Previously, greater surface compliance has been associated with greater leg stiffness and enhanced running economy, suggesting that increased shoe compliance could induce similar effects and therefore at least partially explain the metabolic benefit of AFTs. However, it remains unclear whether midsole compliance replicates the effects of surface compliance on running economy and leg stiffness and what biomechanical mechanisms underlie these improvements.